Ocena hydrauliczna warunków pracy sieci wodociągowej w Łężycy w gminie Zielona Góra = Estimation of hydraulic work conditions of water pipe network in Łężyca in Zielona Góra commune - Ogiołda, Ewa; Uchman, Agata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of water network in Łężyca in Zielona Góra comnmune carried out with EPANET are presented in this paper. They make possible to evaluate parameters of both current water consumption and simulation calculation ? for conditions of water demand designed in future. Conclusions should be important for exploitators of water network.
Keywords: sieć wodociągowa; obliczenia hydrauliczne; obliczenia symulacyjne; water network; hydraulic calculation; simulation calculation